The Way - Sheen, Martin; Estevez, Emilio, 1962-; Unger, Deborah Kara.; Nesbitt, James, 1965-; ARC Entertainment (Firm) (Santa Monica, CA : Arc Entertainment, 2012)
Tom goes to St. Jean Pied de Port, France, to collect the remains of his adult son, who was killed while walking the Camino de Santiago. Tom decides to embark on the pilgrimage to honor his son.
Special features: commentary by Martin Sheen, Emilio Estevez, and David Alexanian; 'Taking The way on the road", featurette; behind the camera; uncovering the characters; 'Along the way', featurette.
Director of photography, Juanmi Azpiroz ; editors, Raul Davalos, Richard Chew ; music, Tyler Bates.
James Nesbitt, Emilio Estevez, Deborah Kara Unger, Martin Sheen.
MPAA rating: PG-13; for some thematic elements, drug use and smoking.
DVD ; widescreen presentation ; Dolby digital 5.1 and stereo.
In English, with optional subtitles in Spanish; closed- captioned.
Keywords: Pilgrims and pilgrimages -- Europe -- Drama; Adult children -- Death -- Drama; Feature films; Action and adventure films; Video recordings for the hearing impaired; Camino de Santiago de Compostela -- Drama